Genus Arisaema: A Review of Traditional Importance, Chemistry and Biological Activities - Kant, Kamal; Lal, Uma R.; Rawat, Ravi; Kumar, Anoop; Ghosh, Manik (Combinatorial Chemistry & High Throughput Screening, 2020)
Background: The Arisaema (Araceae) is a genus of approximately 180 perennial herbs widely distributed in the evergreen and deciduous forests. This genus (Arisaema) has been used as a medicinal agent since ancient times. Experimental investigations have shown a promising positive correlation with its folklore claim and this encourages us to report updated medicinal review (genus Arisaema) for future research. Objective: This review aimed to summarize the ethnobotany, folklore uses, chemistry and biological activities. Conclusion: The comprehensive literature on genus Arisaema indicates the presence of terpenoids, flavonoids, and glycosphingolipids as the principal chemical constituents. Additionally, phytosterols, alkaloids, carboline derivatives and miscellaneous compounds were documented in plants of genus Arisaema. Biological investigations led to the credentials of antioxidant, anticancer, insecticidal, antimicrobial, anthelmintic and hepatoprotective activities. Following, several plant species are promising candidates for the treatment of cancer, parasitic diseases and microbial infection complications. Though, a lot of facets of this genus like phytoconstituents identification, mechanistic profile, adverse effects and clinical studies are still quite limited. Thus, this systematic review may act as a powerful tool in future studies for promoting health benefits against various health hazards.
Keywords: anticancer